Antidiabéticos orais (metformina e gliburida) no tratamento do diabetes mellitus gestacional (DMG): revisão sistemática com metanálise - Paulo Fernando Otaviano Meira (2013)
Gestational diabetes mellitus (GDM) is a common medical problem after pregnancy, especially in the second and third quarters. Hyperglycemia is associated with adverse pregnancy outcomes in women with gestational diabetes mellitus. The main approach for its control is dietary therapy with or without physical activity, with the addition of insulin when these interventions are not enough. Despite representing an effective therapy to control maternal glycemia, insulin administration is costly and inconvenient, requiring skill to handling. In addition to the high cost of insulin therapy, there is a high complexity in relation to their use and rejection of patients to treatment. Thus, the use of oral hypoglycemic agents has been recommended as a cheaper option, simple and easy to accept for treatment of GDM. However, security risks and possible treatment options are not completely known, leading questions for this therapeutic indication. In total, 1819 pregnant women diagnosed with GDM participated in 9 studies included. Of these 621 were treated with metformin, glyburide with 454 and 744 insulin. The total number of participants per study ranged 23-733. The mean gestational age of entry in each intervention group in the studies ranged between 25.44 and 30.8 weeks. The BMI ranged between 22.82 and 39.70. Type studies randomized controlled trial comparing drug regimens for treatment of patients with gestational diabetes mellitus (GDM) including: oral antidiabetic (glyburide and metformin) and insulin at any dose. There was no evidence of increased adverse maternal and neonatal outcomes with the use of glyburide and metformin compared with insulin.